Strategies For Developing Thinking For The Professional And Cultural Education Of Future Teachers Using Gender Models (Eurasian Research Bulletin, 2025)
This research paper explores strategies for developing thinking that can be used for the professional and cultural education of future teachers, with a particular focus on the use of gender models. The paper highlights the importance of incorporating a gender perspective into teacher education programs. By reviewing current literature on developing thinking, gender studies, and educational methodologies, this paper provides a comprehensive framework for integrating gender models into teacher education, developing critical thinking skills, and promoting gender-sensitive pedagogy. The strategies discussed in this paper aim to equip future teachers with the knowledge and skills necessary to effectively address gender-related issues in the classroom and contribute to the development of a more inclusive society